Kontribusi Pengalaman Mengajar, Motivasi Berprestasi dan Supervisi Akademik Terhadap Kinerja Guru SD Mitra Eduversal Seluruh Indonesia - Hartina, Vera; Supriyoko, Supriyoko (Media Manajemen Pendidikan, 2025)
This study aims to determine the contribution of teaching experience, achievement motivation, and academic supervision by school principals to the performance of teachers at Eduversal partner elementary schools across Indonesia. This quantitative research employed a correlational approach and was conducted in six elementary schools from various regions, involving 270 teachers. A sample of 161 teachers was selected using Proportional Random Sampling and the Slovin formula. The research instruments were validated using product-moment correlation, and their reliability was tested with Cronbach’s Alpha. Preliminary analyses included tests for normality, linearity, and multicollinearity. Hypothesis testing was conducted using multiple regression analysis and partial correlation analysis. The findings revealed that collectively, teaching experience, achievement motivation, and academic supervision by school principals positively and significantly contributed to teacher performance. However, individually, teaching experience did not have a significant contribution, indicating that longer work experience does not necessarily lead to improved performance. In contrast, both achievement motivation and academic supervision by school principals individually showed positive and significant contributions, suggesting that higher teacher motivation and stronger academic supervision enhance teacher performance at Eduversal partner elementary schools across Indonesia.